2016
DOI: 10.1159/000448223
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Stress Effects of <b><i>Salvia przewalskii</i></b> Extract in Experimentally Injured Podocytes

Abstract: Background: Oxidative stress is a leading cause of puromycin aminonucleoside (PAN)-induced nephrosis. As the inhibition of oxidative stress may improve injury of podocyte, we aimed at examining the effect of total phenolic acid extract of Salvia przewalskii (SPE) on PAN-induced oxidative stress in vivo and in vitro. Methods: Seventy-two male Sprague-Dawley rats were randomly assigned into 6 groups (n = 12), PAN alone, tacrolimus (TAC), SPE (50, 100 and 200 mg/kg) and normal control group. Salvianolic acid B (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
(41 reference statements)
0
12
0
2
Order By: Relevance
“…In previous studies, we [15] and other groups [16,17] observed that mitochondrial fragmentation was involved in podocyte injury in cultured podocytes. In addition, our previous study found a correlation between the overproduction of glomerular mitochondrial fission proteins, including Drp1, phospho-Drp1 (Ser616) and Fis1, and proteinuria in adriamycin nephropathy in rats [18].…”
Section: Introductionmentioning
confidence: 77%
“…In previous studies, we [15] and other groups [16,17] observed that mitochondrial fragmentation was involved in podocyte injury in cultured podocytes. In addition, our previous study found a correlation between the overproduction of glomerular mitochondrial fission proteins, including Drp1, phospho-Drp1 (Ser616) and Fis1, and proteinuria in adriamycin nephropathy in rats [18].…”
Section: Introductionmentioning
confidence: 77%
“…Osim što ispoljava protektivni efekat protiv direktnog dejstva slobodnih radikala, utvrđeno je i da štiti od toksičnih dejstava lekova na kardiomiocitima (20,21). Pokazano je i da Sal B, zahvaljujući svom antioksidativnom kapacitetu, sprečava oksidativna oštećenja mitohondrijske DNK in vitro i in vivo u ćelijama bubrega (22).…”
Section: Uvodunclassified
“…Ovi rezultati su u skladu s podacima studije u kojoj je utvrđeno da u terapijskoj koncentraciji od 50 μg/ml, čak i u dvostruko većoj koncentraciji od terapijske (100 μg/ml), preparati koji sadrže Sal B nisu značajno uticali na normalnu sintezu DNK u kardiomiocitima, dok tek u koncentraciji većoj od 200 μg/ml mogu da dovedu do smanjene sinteze DNK (36). S druge strane, pokazano je da Sal B ima sposobnost da redukuje oksidaciju mitohondrijske DNK i produkciju 8-OHdG u ćelijama bubrega in vitro i in vivo (22). vitro.…”
Section: Diskusijaunclassified
“…Our previous study showed that SPE can reduce proteinuria, protect podocyte cytoskeletons and restore the expression of genes critical for podocyte structure and function in rats with nephrosis induced by PAN [ 5 ]. Our further study showed that SPE also attenuates the production of 8-OHdG in PAN nephrosis [ 6 ]. SPE and the monomers can reduce ROS production and prevent mitochondrial fission in PAN-treated podocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant effect of high-dose SPE and SalB in PAN-treated cultured podocyte is through suppression of ROS production and mitochondrial fission. In addition, we also found that SPE, SalB and RA can suppress PAN-induced apoptosis in podocytes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%